Improved Biometric Authentication Using Blockchain Based Biometric Authentication Model - Kavitha, M. S.; Sudhakar, Annapantula; Srinivas, KNH; Rani, Paritala Jhansi; B. K., Harsha; Hussain, Sk. Riyaz (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In recent decades, Biometric Blockchain Authentication Models are becoming an optimal model on convenience and safety.With user enrolment on the system based on biometric details, the information is management by the administration model as a template and using this the authentication is conducted via an authentication module.Biometric is one of the safest waysover different applications that secures the data in the form of passwords. However, it suffers mostly from the attacks due to leakage of biometric information that prunes the access of intruders. In this paper, we develop a blockchain based security model for the Biometric Blockchain Authentication Model to secure the data and avoids data leakage. The model is designed in such a way that it verifies and secures the entire data in block ledgers. The experimental validation is conducted to test the efficacy of authentication. The results of simulation show that the proposed authentication model achieves higher degree of security than other methods.